Synthesis and Characterization of new D-π-D Type Schiff Base Ligands by 1,10-Phenanthroline Derivatives and its Complexes with Ruthenium(II) - Erden, Ibrahim (Asian Journal of Chemistry, 2010)
The Schiff base ligands L1 and L2 with D-π-D type have been synthesized from the reaction of 5-amino-1,10-phenanthroline and 5,6-diamino-1,10-phenanthroline with 2-(hexyloxy)-benzaldehyde. The ruthenium(II) complexes of these ligands were prepared and characterized. The ligands L1, L2 and ruthenium complexes have been characterized by FTIR, UV-visible, 1H NMR and fluorescence spectra, as well as, elemental analyses and mass spectra.